PENGARUH MENULIS AL QURAN TERHADAP KADAR GULA DARAH PADA LANSIA DI WANTI WREDHA BISMA UPAKARA PEMALANG - Nunung Hasanah; Santoso Tri Nugroho; Sri Mumpuni Yuniarsih (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2022)
In the elderly, the hormone system is declines..stimulation of the pancreatic response is decreases, so the insulin produced also tends to decrease, than causes an increase in blood glucose. The pancreas is an organ that produces insulin a hormone that regulates the breakdown of glucose and other nutrients in the body. Complementary techniques prove effective methods for lowering blood glucose, namely listening to the recitation of the Qur'an. This study is a quantitative study with a pre-experimental one group pre post test design with a sample of 16 people. Based on the results of the study, it was found that there was no effect of giving an intervention in writing the Quran with the follow the line method on the results of checking blood glucose levels in the elderly at the Bisma Upakara Social Service Orphanage, Pemalang. The hypothalamus is an area that regulates some of the vegetative functions, endocrine functions of the body such as aspects of emotional behavior, and conducts impulses to autonomic fibers that affect the contraction and relaxation of organs. This relaxation can lower blood glucose levels.